Release of IL-1β Triggered by Milan Summer PM10: Molecular Pathways Involved in the Cytokine Release. (6th February 2013) - Bengalli, Rossella; Molteni, Elisabetta; Longhin, Eleonora; Magne, Refsnes; Camatini, Marina; Gualtieri, Maurizio
Abstract : Particulate matter (PM) exposure is related to pulmonary and cardiovascular diseases, with increased inflammatory status. The release of the proinflammatory interleukin- (IL-) 1 β, is controlled by a dual pathway, the formation of inactive pro-IL-1 β, through Toll-like receptors (TLRs) activation, and its cleavage by NLRP3 inflammasome. THP-1-derived macrophages were exposed for 6 h to 2.5 μ g/cm 2 of Milan PM10, and the potential to promote IL-1 β release by binding TLRs and activating NLRP3 has been examined. Summer PM10, induced a marked IL-1 β response in the absence of LPS priming (50-fold increase compared to unexposed cells), which was reduced by caspase-1 inhibition (91% of inhibition respect summer PM10 -treated cells) and by TLR-2 and TLR-4 inhibitors (66% and 53% of inhibition, resp.). Furthermore, summer PM10 increased the number of early endosomes, and oxidative stress inhibition nearly abolished PM10 -induced IL-1 β response (90% of inhibition). These findings suggest that summer PM10 contains constituents both related to the activation of membrane TLRs and activation of the inflammasome NLPR3 and that TLRs activation is of pivotal importance for the magnitude of the response. ROS formation seems important for PM10 -induced IL-1 β response, but further investigations are needed to elucidate the molecular pathway by which this effect is mediated.